PERGESERAN NILAI-NILAI RELIGIUS KENDURI DALAM TRADISI JAWA OLEH MASYARAKAT PERKOTAAN - Windyasari, Shelia (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret)
Abstract The aims of the research are to find out: (1) The types of kenduri tradition done by javanese society. (2) The meaning and philosophy elements consisted in kenduri. (3) The changing of kenduri?s religious values inthe subdistrict of Magetan. The methodology of this research was qualitative descriptive. It used a single fixed case study. The data sources were object, places, events, informants and documents. The technique of collecting data were observation, interviews, and documents analysis. The technique of sampling was purposive sampling. This research used two triangulation techniques to find out the validity of the data namely triangulation data and triangulation method. Technique of analyzing data was interactive analysis. Based on the research can be concluded: (1) The religious sect of the major society of Magetan regency is NU-Moslem. As Javaness society believe NU-Moslem, the society in the subdistrict of Magetan keep the javaness traditions well. (2) The advance of era development, the increasing of knowledge, cause the the society in the subdistrict of Magetan make a reconditional implementation for the ritual of kenduri and it changes the religious values on the ritual. (3) The reconditional of the kenduri ceremony done by the society in the subdistrict of Magetan occured for many reasons. (4) The positive effect of the phenomenon is the society islamic quality increasing, whereas the negative effect kenduri is not in line anymore with the basic purpose